Types of Knowledge in Post-Scientistic Society - Kobylarek, Aleksander (Journal of Education Culture and Society, 2024)
At times of informational deluge, the man in the street is especially vulnerable to the harmful influence of media, to which not only closed groups of people sharing the same beliefs and views contribute but also bots and trolls spreading fake news in the form of conspiracy theories, misinformation, disinformation and propaganda. This audience without proper education and not reflecting on the information gained, can spread more information of this type. Scholars closed in their own reality, conceived of only their inerrancy not only are unable to support, but also are not conducive to the development of science. They also vilify people having different views and the representatives of other disciplines, which they consider inferior. This introduction presents the value of different types of knowledge, not only the scientific ones, and shows its importance for people who may not have other possibilities to learn and understand true science which indicates the meaning of knowledge, which is accessible for people without an academic education. Different types of knowledge, even the seemingly non-scientific type, are the basics for human development and learning. The key to this development, however, is teaching critical thinking. Essential for any change is also the proper choice of academic powers, appreciating and supporting researchers who really affect science, apart from the closed environment of faithful fanatics, and who are able to do science at a global level.